Kann es eine Geographie ohne Raum geben? Zum Verhältnis von Theoriediskussion und Disziplinpolitik - Pohl, Jürgen (ERDKUNDE, 1993)
The question: Is geography possible without space? will be answered from a pragmatic point of view. Regarding the academic disciplines from this position, space is declared as the essential concept of geographical cohesion. This is almost the only shared theoretical frame. Geography without space seems to be impossible. To declare space as the domain of geography does not protect geography from attempts by other disciplines to compete in this field. And other disciplines are concerned with the spatial dimension more and more. The problems of the world society and the corresponding globalization do not cause the spatial dimension to disappear, but give space a new quality. The differentiation of modern society and its internal boundaries are more and more expressed by spatial codes. The position of geography is not improved automatically by the increasing attention given to space. Geography, as the self-declared science of space, is sometimes asked for conceptual help which it cannot give sufficiently. Such a situation demands more theoretical reflecting. Now it becomes clear that geography is not a discipline with a real paradigm in the sense of KUHN, but is merely concentrated around the vague term space. Other disciplines, however, look for the spatial dimension from a theoretical background. In this situation the discussion about spatial concepts promoted by the theoretical geography of the late sixties should be renewed and continued. Perhaps this could give way to the topics concerning the spatial dimension of society. Space is to be regarded as a medium of social processes. Difficulties in this perspective exist because of the ambiguous concept of space. Starting from the platonic chora, geography might reduce conceptual difficulties and perhaps find an answer to the question: what is geography still good for?